2019
DOI: 10.1016/j.jmmm.2018.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic freezing transition in a CoO/Permalloy bilayer revealed by transverse ac susceptibility

Abstract: We utilize variable-temperature, variable-frequency magneto-optical transverse magnetic susceptibility technique to study the static and dynamical magnetic properties of a thin-film CoO/Permalloy bilayer. Our measurements demonstrate that in the studied system, the directional asymmetry of the hysteresis loop is associated mainly with the difference in the reversal mechanisms between the two reversed states of magnetization stabilized by the exchange-induced uniaxial anisotropy. The latter is found to be much … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Qualitatively, we attribute the surprising difference between the characteristics for the two opposite field directions to the exchange-spring effects in CoO, which may produce quasi-uniform exchange torque over length scales comparable to the grain size of polycrystalline CoO. We also note that our surprising observations are consistent with a recent observation, for similar Permalloy/CoO bilayers, of qualitatively different reversal mechanisms between the two opposite directions of Py magnetization 31 . Specifically, transverse ac susceptibility measurements showed that magnetization reversal from the magnetization direction opposite to the field-cooling direction into the direction aligned with the latter, occurs as soon as its energy becomes higher.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Qualitatively, we attribute the surprising difference between the characteristics for the two opposite field directions to the exchange-spring effects in CoO, which may produce quasi-uniform exchange torque over length scales comparable to the grain size of polycrystalline CoO. We also note that our surprising observations are consistent with a recent observation, for similar Permalloy/CoO bilayers, of qualitatively different reversal mechanisms between the two opposite directions of Py magnetization 31 . Specifically, transverse ac susceptibility measurements showed that magnetization reversal from the magnetization direction opposite to the field-cooling direction into the direction aligned with the latter, occurs as soon as its energy becomes higher.…”
Section: Discussionsupporting
confidence: 91%
“…by reactive sputtering in ultrapure oxygen atmosphere, with the partial pressure of oxygen optimized as in our previous studies of CoO-based systems 29,31,38 .…”
Section: Methodsmentioning
confidence: 99%
“…Ta(2) served as a capping layer protecting the films from oxidation. The thickness of 8 nm for CoO was above the transition to the Heisenberg domain state (HDS) at t ≈ 6 nm, minimizing the glassy magnetic dynamics of the AF magnetic order driven by the Py magnetization [18,33]. Nevertheless, our data provide evidence of spin flop reversal in AF, which is expected even for large AF thickness [35].…”
Section: Ii1 Sample Preparationmentioning
confidence: 59%
“…The multilayers were deposited in a 150 Oe in-plane magnetic field, which is known to facilitate magnetic ordering in CoO. Py and Ta were deposited by dc sputtering from the stoichiometric targets in 1.8 mTorr of ultrapure Ar, while CoO was deposited from a Co target by reactive sputtering in a mixture of ultrapure oxygen and Ar, with the partial pressure of oxygen optimized as in our previous studies of CoO-based systems [15,18,33,36]. Measurements below the Nèel temperature T N = 290 K of CoO, were performed after cooling from room temperature (RT) in the presence of an external magnetic field H dc = 0.5 kOe.…”
Section: Ii1 Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation